The Effect of L- Carnitine on Cardiac Output in Patient with Chronic Kidney Disease on Regular Hemodialysis - Abdul-Hassan Mahdi S.; Abdul-Aziz A.A. (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: L- carnitine deficiency is common in patients with chronic kidney disease, especially thosewho are in regular dialysis. L- carnitine deficiency associated with high incidence of oxidative stress,dyslipidemia and impaired cardiac performance. The present study tends to evaluate the effect of L-carnitinesupplement on cardiac output in patients with chronic kidney disease on regular hemodialysis.Methods: the current study included 105 patients with chronic kidney disease, they were randomly selectedfrom patients attending artificial kidney unit at Al-Hussein Teaching Hospital in Thiqar city for regularhemodialysis. They were divided into two groups, group I include 35 patients with chronic kidney diseasewho did not receive L- carnitine and considered as control group, group II include 70 patients with chronickidney disease who receive L- carnitine. patients of group II further divided into two subgroups depending ondose of L- carnitine. Group II(A), include 35 patients with chronic kidney disease who received L- carnitine10/kg body weight one time daily and group II(B): include 35 patients with chronic kidney disease whoreceived L- carnitine 10/kg body weight two time daily. Ejection fraction was determined by transthoracicechocardiography. Frequency, percentage, association, paired t-test were used for analysis of variables. Allvariables represented by mean ± SD. P value of < 0.05 considered statistically significant.Results: There was statistically significant increase in the mean of EF% (P<0.001) among patients withchronic kidney disease who receive L- carnitine in a dose of 10mg/Kg body weight twice daily (group IIB)after six months of treatment in comparison with the baseline values. There was a slight but significant (p<0.05) increase in the mean of EF% in patients with chronic kidney disease who received single daily doseof L- carnitine 10mg/Kg body weight (group IIA) after six months in comparison with the initial values atthe beginning of the study. Conclusion: carnitine supplement in a suitable dose seem to improve cardiac performance among patientswith chronic kidney diseases on regular hemodialysis.